Population pharmacokinetics of meropenem in critically ill children with different renal functions - Rapp, Mélanie; Urien, Saïk; Foissac, Frantz; Béranger, Agathe; Bouazza, Naïm; Benaboud, Sihem; Bille, Emmanuelle; Zheng, Yi; Gana, Inès; Moulin, Florence; Lesage, Fabrice; Renolleau, Sylvain; et al. (European journal of clinical pharmacology, 2020)
Purpose We aimed to develop a meropenem population pharmacokinetic (PK) model in critically ill children and simulate dosing regimens in order to optimize patient exposure. Methods Meropenem plasma concentration was quantified by high-performance liquid chromatography. Meropenem PK was investigated using a non-linear mixed-effect modeling approach. Results Forty patients with an age of 16.8 (1.4–187.2) months, weight of 9.1 (3.8–59) kg, and estimated glomerular filtration rate (eGFR) of 151 (19–440) mL/min/1.73 m 2 were included. Eleven patients received continuous replacement renal therapy (CRRT). Concentration-time courses were best described by a two-compartment model with first-order elimination. Body weight (BW), eGFR, and CRRT were covariates explaining the between-subject variabilities on central/peripheral volume of distribution (V1/V2), inter-compartment clearance ( Q ), and clearance (CL): V1 i = V1 pop × (BW/70) 1 , Q i = Q pop × (BW/70) 0.75 , V2 i = V2 pop × (BW/70) 1 , CL i = (CL pop × (BW/70) 0.75 ) × (eGFR/100) 0.378 ) for patients without CRRT and CL i = (CL pop × (BW/70) 0.75 ) × 0.9 for patients with CRRT, where CL pop , V1 pop , Q pop , and V2 pop are 6.82 L/h, 40.6 L, 1 L/h, and 9.2 L respectively normalized to a 70-kg subject. Continuous infusion, 60 and 120 mg/kg per day, is the most adequate dosing regimen to attain the target of 50% f T > MIC and 100% f T > MIC for patients infected by bacteria with high minimum inhibitory concentration (MIC) value (> 4 mg/L) without risk of accumulation except in children with severe renal failure. Conclusion Continuous infusion allows reaching the f T > MIC targets safely in children with normal or increased renal clearance.